Global, regional and local similarities and differences in HRM in light of Cranet researches (2008-2016) - Poór, József; Kovács, Ildikó; Karoliny, Zsuzsa; Machova, Renata (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
Approaching management sciences is based on empirical analysis of the facts and phenomena. In the research field of Human Resource Management (HRM) there has always been a need to explore and explain the similarities and differences in HRM practice of diverse countries. To do so, various national cultural and institutional characteristics used to be considered by comparative HR research on IHRM practices. The studies also target not only to examine whether country groups or regions can be detected with distinctive HRM characteristics but also to search for the explanatory factors of it. Following contextual research paradigm this paper is trying to find an answer for the question: what characteristic features the HRM practice of Central and Eastern European countries show compared to the current global tendencies. In addition to theoretical approaches related to HRM, the study follows the conceptual framework provided by cultural clusters and comparative economics.